Inovasi Paving Block Berbasis Daur Ulang Sampah Plastik di Desa Kartoharjo: Penelitian - Aldo Robby Pradana; Addina Nur Afifah; Desyka Rizky Irmaningtyas; Dwi Amalia Rahmawati; Khilmak Akmila; Luluk Mushoffa; Miftah Ali Masruron; Muhamad Yasin Yusuf Al Asyuro; Al Asyuro; Ni’matul Anisa’; Putri Maratus Sholikhah; Reisyana Azizah; Rizky Ramadhan; Romi Robig Indra Susila; Vanezta Realy Vieo (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Plastic waste in Kartoharjo Village, Magetan Regency, poses a serious environmental challenge due to the community’s low awareness of waste segregation and independent waste management. The accumulation of non-biodegradable plastic waste negatively affects environmental cleanliness and public health. This study aims to provide a practical solution through the innovation of processing plastic waste into durable, cost-effective, and environmentally friendly paving blocks. The method employed was participatory action learning, engaging the community actively from problem identification, material collection, and technical training to the production process. Data were collected through preliminary surveys, in-depth interviews with village leaders, and participatory observation during the activities. The findings reveal that this innovation significantly reduces plastic waste volume, raises public awareness of recycling, and creates new entrepreneurial opportunities. The produced paving blocks are lightweight, water-resistant, moss-resistant, and suitable for local-scale construction. Socialization and training sessions conducted on July 29, 2025, were enthusiastically received, as reflected in active participation and the willingness of residents to apply the skills independently.